Gaya Kepemimpinan berbasis Emotional Intelligence - Hamim Tohari (Jurnal Kependidikan)
This paper is intended to provide input to school principals or leaders of educational institutions to not only pay attention to aspects of intellectual and spiritual intelligence in the use of leadership style, but also attention to aspects of emotional intelligence because this aspect has an important role in interacting with subordinates. Emotional intelligence is interpreted as the ability to listen to emotional whispers, and make it an important source of information to understand yourself and others to achieve a goal. If the principal can use this emotional intelligence well, the emotional relationship between the principal and teachers and employees will always be maintained and is expected to improve the performance of subordinates in achieving organizational goals. There are six leadership styles based on emotional intelligence mentioned by Goleman, i.e. visionary , mentor, affiliative, democratic, speed determinant, and authoritarian leadership styles. However, the principle should apply this styles of leadership proportionaly.